Penerapan Model Pembelajaran Kooperatif Tipe Teams Games-Tournament dengan Menggunakan Media Kartu Cetak untuk Meningkatkan Hasil Belajar - Mamanda, Slamet; Sumantri, Made (Journal of Education Action Reseach, 2018)
This study aims to determine the improvement of the ability of students of class IVA Semester I in SDN1 Banjar Jawa, Lesson Year 2017/2018 on the subject of Civics after the application of cooperative learning model of Teams Games Tournament. This type of research is a classroom action research carried out in a prayer cycle. Each cycle consists of planning, execution, or evaluation. The subjects of the study were students of IVA SDN 1 Banjar Jawa, 41 people, 22 female students and 19 male students. The data of the research showed that in the first cycle students achievement classically reached 87.80% with an average score of 76.22 and the activity of active categorized students with a score of 30.25 and teacher activity categorized well with score 23. In period II Learning outcomes students increased to 90.24% with an average of 78.05 and very active categorized student activity with a score of 33.75 and teacher activity categorized very well with a score of 25. Thus, the application of cooperative learning model of Team Games Tournament type with assisted media card information can improve student learning outcomes grade IV SDN 1 Banjar Jawa on subjects Civics Lesson 2017/2018.